Catalyst for preparing light olefins from synthesis gas, preparation method and application thereof

By preparing catalysts containing elements such as manganese, copper, calcium and dysprosium, the problems of low CO conversion rate and low carbon olefin selectivity of existing catalysts are solved, and efficient preparation of low carbon olefins and catalyst stability are achieved.

CN115990499BActive Publication Date: 2025-02-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111224684.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-20
Publication Date
2025-02-07
Estimated Expiration
2041-10-20

AI Technical Summary

Technical Problem

The existing catalysts that directly produce low-carbon olefins in synthesis gas have problems such as low-CO conversion rate, low-carbon olefin selectivity, and poor catalyst stability.

Method used

Provide a new catalyst whose active component is the chemical formula of Fe100MnaCubCrcDdEeOx, which contains elements such as manganese, copper, calcium and dysprosium. The carrier is silica, alumina or titanium oxide. It is mixed, precipitated, dried and molded, and reduced by specific precursors. and carbonization treatment to form a catalyst with a χ-Fe5C2 crystal plane.

Benefits of technology

In the process of directly preparing low-carbon olefins in the synthesis gas, this catalyst has a high CO conversion rate, good selectivity of low-carbon olefins and good stability, which can effectively improve the reaction efficiency and product purity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115990499B_ABST
    Figure CN115990499B_ABST
Patent Text Reader

Abstract

The present invention discloses a catalyst for preparing light olefins from synthesis gas, and a preparation method and application thereof. The catalyst for preparing light olefins from synthesis gas of the present invention has a χ-Fe5C2 crystal face, and the catalyst comprises a carrier and an active component, wherein the chemical formula of the active component is as follows in terms of atomic ratio: Fe 100 Mn a Cu b Cr c D d E e O x , D is selected from at least one of alkaline earth metals; E is selected from at least one of lanthanide rare earth elements; a is in the range of 30.0 to 120.0; b is in the range of 5.0 to 50.0; c is in the range of 1.0 to 30.0; d is in the range of 0.1 to 10.0; and e is in the range of 0.1 to 10.0. When the catalyst of the present invention is used for directly preparing light olefins from synthesis gas, it has the advantages of higher CO conversion rate, better selectivity of light olefins, and better catalyst stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalysts, and in particular to a catalyst for preparing light olefins from synthesis gas and a preparation method thereof, as well as a method for directly preparing light olefins from synthesis gas. Background Art

[0002] The direct reaction process of syngas to light olefins is relatively complicated, and there is still some controversy about the active phase of the catalyst, but it is generally believed that the active center is Fe x C y This type of catalyst is usually synthesized in the form of metal oxides. Therefore, before the direct reaction of synthesis gas to light olefins, the catalyst must be activated and pretreated to make the catalyst active. Since this type of catalyst is generally composed of multiple metal elements, the iron carbide phase is diverse and complex, and the catalytic activity exhibited under different conditions is also different.

[0003] CN1704161A discloses a molten iron catalyst for Fischer-Tropsch synthesis and its preparation method and application. The catalyst comprises: a molar ratio of trivalent iron to twice divalent iron Fe 3+ / 2Fe 2+ The catalyst has a mass fraction of 0.20-1.40 and a mass fraction of 65-71% of iron (Fe). In addition, the catalyst also includes a co-catalyst, which is composed of 0.1-3.6 g / 100 g of aluminum oxide (Al2O3), 0.1-1.4 g / 100 g of potassium oxide (K2O), 0.1-2.5 g / 100 g of calcium oxide (CaO), and 0-5.0 g / 100 g of other oxides. However, the catalyst has problems such as low CO conversion rate, low selectivity of light olefins, and poor catalyst stability. Summary of the invention

[0004] In view of the above problems existing in the prior art, the present invention provides a new catalyst for preparing light olefins from synthesis gas and a preparation method thereof. When the catalyst of the present invention is used to directly prepare light olefins from synthesis gas, it has the advantages of higher CO conversion rate and better selectivity for light olefins, and the catalyst has better stability.

[0005] The first aspect of the present invention provides a catalyst for preparing light olefins from synthesis gas, the catalyst having a χ-Fe5C2 crystal face, the catalyst comprising a carrier and an active component, wherein the chemical formula of the active component is as follows, calculated by atomic ratio:

[0006] Fe 100 Mn a Cu b Cr c D d E e O x ,

[0007] D is selected from at least one of alkaline earth metals;

[0008] E is selected from at least one of the lanthanide rare earth elements;

[0009] The value range of a is 30.0~120.0;

[0010] The value range of b is 5.0~50.0;

[0011] The value range of c is 1.0~30.0;

[0012] The value range of d is 0.1~10.0;

[0013] The value range of e is 0.1~10.0;

[0014] x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst.

[0015] According to some embodiments of the present invention, the crystal spacing of the catalyst is

[0016] According to some embodiments of the present invention, preferably, the alkaline earth metal is selected from at least one of Be, Mg, Ca, Sr and Ba.

[0017] According to some embodiments of the present invention, preferably, the lanthanide rare earth element is selected from at least one of La, Ce, Pr and Nd.

[0018] According to some embodiments of the present invention, preferably, the value range of a is 40.0-110.0; the value range of b is 10.0-40.0; the value range of c is 5.0-25.0; the value range of d is 0.5-8.0; and the value range of e is 0.5-8.0.

[0019] According to some embodiments of the present invention, preferably, the carrier is selected from at least one of silica, alumina and titania.

[0020] According to some embodiments of the present invention, preferably, the content of the carrier is 5 to 60 wt % based on the weight of the catalyst.

[0021] The second aspect of the present invention provides a method for preparing a catalyst for preparing light olefins from synthesis gas, comprising:

[0022] (1) mixing a solution containing an Fe precursor with a solution containing a Mn precursor, a Cu precursor, and a Cr precursor to obtain a solution I;

[0023] (2) precipitating the solution I with an alkaline precipitant, and washing the precipitate to obtain a precipitate;

[0024] (3) mixing the precipitate with a carrier sol and an alkaline earth metal precursor solution in sequence, adjusting the pH value of the slurry, mixing with a lanthanide rare earth element precursor solution, drying, forming and calcining to obtain an iron-based catalyst intermediate;

[0025] (4) The iron-based catalyst intermediate is subjected to reduction treatment and carbonization treatment.

[0026] According to some embodiments of the present invention, preferably, the reduction treatment conditions include: a pressure of 0 to 2 MPa.

[0027] According to some embodiments of the present invention, preferably, the reduction treatment conditions include: catalyst loading 3000-6000 mL·h -1 ·g -1 .

[0028] According to some embodiments of the present invention, preferably, the reduction treatment conditions include: a temperature of 200 to 550°C.

[0029] According to some embodiments of the present invention, preferably, the reduction treatment conditions include: a time of 12 to 48 hours.

[0030] According to some embodiments of the present invention, preferably, the reduction treatment conditions include: a heating rate of 1 to 15° C. / min.

[0031] According to some embodiments of the present invention, preferably, the reduction treatment conditions include: the reduction treatment atmosphere is a mixed gas containing H2 and N2.

[0032] According to some embodiments of the present invention, preferably, based on the total volume of the mixed gas, the volume concentration of H2 is 1% to 20%, and the volume concentration of N2 is 80% to 99%.

[0033] According to some specific embodiments of the present invention, the reduction treatment includes:

[0034] (1) using H2 / N2 gas with H2 volume concentration of 1% to 20% (H2 volume concentration of 1% to 20%, N2 volume concentration of 80% to 99%, and the total is 100%), and heating at 1 to 15°C / min to 200 to 550°C;

[0035] (2) At a pressure of 0 to 2 MPa and a catalyst load of 3000 to 6000 mL·h -1 ·g -1 , maintain 200-550℃ for 12-48 hours.

[0036] According to some embodiments of the present invention, preferably, the carbonization treatment conditions include: a pressure of 0 to 2 MPa.

[0037] According to some embodiments of the present invention, preferably, the carbonization treatment conditions include: the catalyst load is 3000-6000 mL·h -1 ·g -1 .

[0038] According to some embodiments of the present invention, preferably, the carbonization treatment conditions include: a temperature of 200-550°C.

[0039] According to some embodiments of the present invention, preferably, the carbonization treatment conditions include: a time of 12 to 48 hours.

[0040] According to some embodiments of the present invention, preferably, the carbonization treatment conditions include: a heating rate of 3 to 20° C. / min.

[0041] According to some embodiments of the present invention, preferably, the conditions for the carbonization treatment include: the atmosphere for the carbonization treatment is a mixed gas containing olefins, CO and N2.

[0042] According to some embodiments of the present invention, preferably, the olefin is C2H4 and / or C3H6.

[0043] According to some embodiments of the present invention, preferably, based on the total volume of the mixed gas, the total volume concentration of olefins and CO is 10% to 60%; the volume concentration of N2 is 40% to 90%. The total is 100%

[0044] According to some embodiments of the present invention, preferably, based on the total volume concentration of olefin and CO, the volume concentration of olefin is 10% to 50%; and the volume concentration of CO is 50% to 90%.

[0045] In the present invention, for example, "20 volume % of a mixture of C2H4 and CO (including 30 volume % C2H4 and 70 volume % CO) / 80 volume % N2 gas" in the embodiments refers to a mixture of 20 volume % C2H4 and CO, and 80 volume % N2; in the mixture, there are 30 volume % C2H4 and 70 volume % CO.

[0046] According to some specific embodiments of the present invention, the carbonization treatment comprises:

[0047] (1) using a (10-50 volume % C2H4 or C3H6:90-50 volume % CO) / N2 gas with a volume concentration of 10% to 60%, and heating the mixture to 200-550°C at a rate of 3-20°C / min;

[0048] (2) At a pressure of 0 to 2 MPa and a catalyst load of 3000 to 6000 mL·h -1 ·g -1 , maintain 200-550℃ for 12-48 hours.

[0049] According to some embodiments of the present invention, preferably, the pH is adjusted to 1-6.

[0050] According to some embodiments of the present invention, preferably, the temperature for precipitating the solution I using an alkaline precipitant is 70-100°C.

[0051] According to some embodiments of the present invention, preferably, the iron precursor may be a soluble salt of iron, such as but not limited to iron nitrate, iron carbonate, and the like.

[0052] According to some embodiments of the present invention, preferably, the Mn precursor and the Cu precursor may be a soluble salt of Mn and a soluble salt of Cu, such as but not limited to manganese nitrate, copper nitrate and the like.

[0053] According to some embodiments of the present invention, preferably, the precursor of Cr may be a nitrate of Cr or an oxide of Cr, such as but not limited to chromium nitrate and chromium oxide.

[0054] According to some embodiments of the present invention, preferably, the precipitant is ammonia water and / or urea.

[0055] According to some embodiments of the present invention, preferably, the alkaline earth metal precursor may be a soluble compound of an alkaline earth metal, such as a nitrate, a carbonate, a chloride or a hydroxide of an alkaline earth metal.

[0056] According to some embodiments of the present invention, preferably, the lanthanide rare earth element precursor may be a soluble salt of the lanthanide rare earth element, such as but not limited to a nitrate of the lanthanide rare earth element.

[0057] According to some embodiments of the present invention, preferably, the process conditions of spray drying molding have a wider selection range, for example, but not limited to, under the conditions that the spray inlet temperature can be 200-380°C, the outlet temperature can be 100-230°C, spray drying is performed to form microspheres, and finally calcination is performed to form a catalyst.

[0058] According to some embodiments of the present invention, preferably, the calcination conditions include: a temperature of 400 to 1000° C., preferably 450 to 800° C.; and a time of 0.15 to 10 hours, preferably 0.5 to 8 hours.

[0059] According to some embodiments of the present invention, preferably, the Fe precursor, the Mn precursor, the Cu precursor and the Cr precursor, the alkaline earth metal precursor and the lanthanide rare earth element precursor are used in an amount such that the prepared catalyst has an active component having the following chemical formula:

[0060] Fe 100 Mn a Cu b Cr c D d E e O x

[0061] D is selected from at least one of alkaline earth metals;

[0062] E is selected from at least one of the lanthanide rare earth elements;

[0063] The value range of a is 30.0~120.0;

[0064] The value range of b is 5.0~50.0;

[0065] The value range of c is 1.0~30.0;

[0066] The value range of d is 0.1~10.0;

[0067] The value range of e is 0.1~10.0;

[0068] x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst;

[0069] The preferred value range of a is 40.0 to 110.0;

[0070] The value range of b is 10.0~40.0;

[0071] The value range of c is 5.0~25.0;

[0072] The value range of d is 0.5~8.0;

[0073] The value range of e is 0.5~8.0.

[0074] According to some embodiments of the present invention, preferably, the amount of the carrier used satisfies that the weight of the carrier is 5 to 60 weight % based on the total weight of the catalyst.

[0075] According to a specific embodiment of the present invention, the preparation method may include but is not limited to:

[0076] (1) dissolving an Fe precursor in water to prepare a solution;

[0077] (2) adding a Mn precursor, a Cu precursor and a Cr precursor to the solution obtained in step (1) to prepare a solution I;

[0078] (3) precipitating solution I with an alkaline precipitant in a water bath at 70-100° C.;

[0079] (4) washing and separating the precipitate to obtain a precipitate;

[0080] (5) adding the precipitate to the required amount of carrier sol, mixing and slurrying;

[0081] (6) adding the prepared alkaline earth metal precursor solution;

[0082] (7) adding an acid-base regulator to adjust the pH value of the slurry to 1 to 6;

[0083] (8) adding the prepared lanthanide rare earth element precursor solution;

[0084] (9) spray-forming and calcining the slurry to obtain an iron-based catalyst intermediate;

[0085] (10) The iron-based catalyst intermediate obtained in step (9) is subjected to reduction treatment and carbonization treatment to obtain a catalyst (iron-based catalyst) for preparing light olefins from synthesis gas.

[0086] The third aspect of the present invention provides a catalyst for preparing light olefins from synthesis gas obtained according to the above-mentioned preparation method, wherein the catalyst has a χ-Fe5C2 crystal face, and the catalyst comprises a carrier and an active component, wherein the chemical formula of the active component is as follows, in terms of atomic ratio:

[0087] Fe 100 Mn a Cu b Cr c D d E e O x

[0088] D is selected from at least one of alkaline earth metals;

[0089] E is selected from at least one of the lanthanide rare earth elements;

[0090] The value range of a is 30.0~120.0;

[0091] The value range of b is 5.0~50.0;

[0092] The value range of c is 1.0~30.0;

[0093] The value range of d is 0.1~10.0;

[0094] The value range of e is 0.1~10.0;

[0095] x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst.

[0096] According to some embodiments of the present invention, the crystal spacing of the catalyst is

[0097] According to some embodiments of the present invention, preferably, the alkaline earth metal is selected from at least one of Be, Mg, Ca, Sr and Ba.

[0098] According to some embodiments of the present invention, preferably, the lanthanide rare earth element is selected from at least one of La, Ce, Pr and Nd.

[0099] According to some embodiments of the present invention, preferably, the value range of a is 40.0-110.0; the value range of b is 10.0-40.0; the value range of c is 5.0-25.0; the value range of d is 0.5-8.0; and the value range of e is 0.5-8.0.

[0100] According to some embodiments of the present invention, preferably, the carrier is selected from at least one of silica, alumina and titania.

[0101] According to some embodiments of the present invention, the content of the carrier is preferably 5 to 60 wt % based on the weight of the catalyst.

[0102] A fourth aspect of the present invention provides a method for directly preparing light olefins from synthesis gas, comprising: in the presence of the above-mentioned synthesis gas for preparing light olefins or the synthesis gas for preparing light olefins obtained according to the above-mentioned preparation method, contacting H2 with CO for reaction.

[0103] According to some embodiments of the present invention, preferably, the reaction temperature is 200-600°C.

[0104] According to some embodiments of the present invention, preferably, the reaction pressure is 0.5-10 MPa.

[0105] According to some embodiments of the present invention, preferably, based on the amount of the pre-reduced catalyst, the volumetric space velocity of the synthesis gas is 100 to 8000 mL·h -1 ·g -1 .

[0106] According to some embodiments of the present invention, preferably, the H2 / CO molar ratio in the synthesis gas is 0.1-5.

[0107] According to some embodiments of the present invention, preferably, the low carbon olefin is a C2-C4 olefin, more specifically ethylene, propylene and butene or a mixture thereof, butene including butene-1, butene-2, isobutylene and butadiene.

[0108] Beneficial effects of the present invention:

[0109] (1) The catalyst for preparing low-carbon olefins from synthesis gas provided by the present invention has manganese as an alkali additive in the active component, which has an electron-donating effect, can change the binding energy of species on the sample surface, and has the effect of improving the selectivity of low-carbon olefins. Introducing the manganese additive into the iron-based catalyst system can also promote the formation of olefins and reduce the content of CH4. The alkali metal additive mainly affects the electronic state of the Fe catalyst surface due to its electron additive effect, increases the electron density on the Fe surface, thereby promoting CO dissociative adsorption and inhibiting the adsorption of H2, thereby increasing the catalyst reaction activity and reducing the methane production. Copper plays a promoting role in the reduction process of iron oxide, reducing the reduction temperature of the catalyst; promoting the chemical adsorption of the iron catalyst, which is beneficial to improving the catalyst activity; and can also promote the formation of carbides of the iron catalyst.

[0110] (2) The catalyst for preparing low-carbon olefins from synthesis gas of the present invention has a χ-Fe5C2 crystal plane with a crystal spacing of It is used in the industrial production of direct production of light olefins from synthesis gas, with high feedstock conversion rate and product selectivity, and good catalyst stability.

[0111] (3) In the process of preparing the catalyst for preparing light olefins from synthesis gas according to the present invention, a (10-50% C2H4 or C3H6: 90-50% CO) / N2 gas with a volume concentration of 10% to 60% is used during carbonization treatment, and the temperature is raised to 200-550°C at 3-20°C / min to perform carbonization treatment, thereby preferably preparing a catalyst having a χ-Fe5C2 crystal plane and a crystal spacing of catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0112] Figure 1 This is a transmission electron microscope photograph (100 nm) of the catalyst for producing light olefins from gas prepared in Example 1 of the present invention.

[0113] Figure 2 This is a transmission electron microscope photograph (5 nm) of the catalyst for producing light olefins from gas prepared in Example 1 of the present invention.

[0114] Figure 3 This is a transmission electron microscope photograph (200 nm) of the catalyst prepared in Comparative Example 1 of the present invention.

[0115] Figure 4 This is a transmission electron microscope photograph (5 nm) of the catalyst prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0116] In order to make the present invention more easily understood, the present invention will be described in detail below in conjunction with embodiments. These embodiments are only for illustration and are not intended to limit the application scope of the present invention.

[0117] The test method of the present invention and the equipment used in the test are as follows:

[0118] The raw materials used in the examples and comparative examples, unless otherwise specified, are all disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0119] In the present invention, TEM (transmission electron microscopy) is performed on a Tecnai 20S-TWIN model with an accelerating voltage of 200 kV. The prepared slurry is subjected to micro-spheroidal molding in a spray dryer, which refers to spray molding using a centrifugal spray dryer. The inlet temperature of the centrifugal spray dryer is 200-380° C., and the outlet temperature is 100-230° C. The crystal phase and intercrystalline distance are obtained by TEM.

[0120] [Example 1]

[0121] Preparation of catalyst for producing light olefins from syngas:

[0122] (1) Take 425.9 g of ferric nitrate, add 1000 g of water and stir to dissolve, then add 147.9 g of 50% manganese nitrate, 25.21 g of copper nitrate and 5.27 g of chromium nitrate in sequence, stir to dissolve to obtain material solution I. Heat the material solution I to 90° C. in a water bath, add ammonia water at a rate of 25 ml / s under stirring to carry out precipitation reaction, then wash and separate the precipitate to obtain a precipitate.

[0123] (2) 312.5 g of 40 wt% silica sol material was taken, and the above precipitate was added under stirring. After mixing, 50 g of a solution containing 1.30 g of magnesium nitrate was added, and the pH value of the above slurry was adjusted with ammonia water so that the pH of the mixed slurry was 6.0. Then, 10 g of an aqueous solution containing 2.30 g of cerium nitrate was added. After the material was fully stirred, the prepared slurry was formed into microspheres in a spray dryer according to the usual method. Finally, a microsphere with an inner diameter of 89 mm and a length of 1700 mm was prepared. The catalyst composition is calcined at 500°C for 2 hours in a rotary calcining furnace: 50 wt% Fe 100 Mn 40 Cu 10.0 Cr 5.0 Mg 0.5 Ce 0.5 O x +50 wt.% SiO2.

[0124] (3) The obtained catalyst was reduced by heating the mixture to 300°C at a rate of 3°C / min using 5% by volume H2 / 95% by volume N2 gas; the mixture was heated to 300°C at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 300℃ for 15 hours.

[0125] (4) The catalyst was carbonized by heating the mixture of 20 vol% C2H4 and CO (30 vol% C2H4, 70 vol% CO) / 80 vol% N2 gas at 5°C / min to 350°C at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 350℃ for 20 hours.

[0126] TEM images of the catalyst after reduction and carbonization treatment are shown in Figure 1 and Figure 2 From the figure, it is obvious that the χ-Fe5C2 crystal phase has a crystal spacing of

[0127] [Example 2]

[0128] Preparation of catalyst for producing light olefins from syngas:

[0129] (1) Take 181.9 g of ferric nitrate, add 1000 g of water and stir to dissolve, then add 173.7 g of 50% manganese nitrate, 43.70 g of copper nitrate and 11.26 g of chromium nitrate in sequence, stir to dissolve to obtain material solution I. Heat the material solution I to 90° C. in a water bath, add ammonia water at a rate of 40 ml / s under stirring to carry out precipitation reaction, then wash and separate the precipitate to obtain a precipitate.

[0130] (2) 336.4 g of 40 wt% aluminum sol material was taken, and the above precipitate was added under stirring. After mixing, 100 g of a solution containing 8.40 g of calcium nitrate was added, and the pH value of the above slurry was adjusted with ammonia water so that the pH of the mixed slurry was 6.0. Then, 100 g of an aqueous solution containing 5.90 g of neodymium nitrate was added. After the material was fully stirred, the prepared slurry was formed into microspheres in a spray dryer according to the usual method, and finally a microsphere with an inner diameter of 89 mm and a length of 1700 mm was formed. The catalyst composition is 40 wt % Fe 100 Mn 110 Cu 40.0 Cr 25.0 Ca 8.0 Nd 8.0 O x+60 wt.% Al2O3.

[0131] (3) The obtained catalyst was reduced by using 5% volume concentration H2 / N2 gas and heating to 300°C at 3°C / min; the catalyst was heated to 300°C at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 300℃ for 15 hours.

[0132] (4) The catalyst was carbonized by heating the mixture of 20 vol% C2H4 and CO (30 vol% C2H4, 70 vol% CO) / 80 vol% N2 gas at 5°C / min to 350°C at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 350℃ for 20 hours.

[0133] TEM images of the catalyst after reduction and carbonization treatment Figure 1 and Figure 2 Similarly, the χ-Fe5C2 crystal phase is clearly visible, and the intercrystalline distance is

[0134] [Example 3]

[0135] The method of Example 1 was followed except that step (4) was carbonized by heating the mixture of 20 vol% C2H4 and CO (10 vol% C2H4, 90 vol% CO) / 80 vol% N2 gas at 5°C / min to 350°C at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h. -1 ·g -1 , 350℃ for 20 hours.

[0136] Finally, the catalyst was obtained, and the TEM image of the catalyst was Figure 1 and Figure 2 Similarly, the χ-Fe5C2 crystal phase is clearly visible, and the intercrystalline distance is

[0137] [Example 4]

[0138] The method of Example 1 was followed except that step (4) was carbonized by heating the mixture of 20 vol% C2H4 and CO (50 vol% C2H4, 50 vol% CO) / 80 vol% N2 gas at 5°C / min to 350°C at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 350℃ for 20 hours.

[0139] Finally, the catalyst was obtained, and the TEM image of the catalyst was Figure 1 and Figure 2 Similarly, the χ-Fe5C2 crystal phase is clearly visible, and the intercrystalline distance is

[0140] [Example 5]

[0141] The method of Example 1 was followed except that step (4) was carbonized by heating the mixture of 60 vol% C2H4 and CO (30 vol% C2H4, 70 vol% CO) / 40 vol% N2 gas at 5°C / min to 350°C at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 350℃ for 20 hours.

[0142] Finally, the catalyst was obtained, and the TEM image of the catalyst was Figure 1 and Figure 2 Similarly, the χ-Fe5C2 crystal phase is clearly visible, and the intercrystalline distance is

[0143] [Example 6]

[0144] The method of Example 1 was followed except that step (4) was carbonized by heating the mixture of 10 vol% C2H4 and CO (30 vol% C2H4, 70 vol% CO) / 90 vol% N2 gas at 5°C / min to 350°C at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 350℃ for 20 hours.

[0145] Finally, the catalyst was obtained, and the TEM image of the catalyst was Figure 1 and Figure 2 Similarly, the χ-Fe5C2 crystal phase is clearly visible, and the intercrystalline distance is

[0146] [Example 7]

[0147] The method of Example 1 was followed except that step (4) was carbonized by heating the mixture of 20 vol% C3H6 and CO (30 vol% C3H6, 70 vol% CO) / 80 vol% N2 gas at 5°C / min to 350°C at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h. -1 ·g -1 , 350℃ for 20 hours.

[0148] Finally, the catalyst was obtained, and the TEM image of the catalyst was Figure 1 and Figure 2 Similarly, the χ-Fe5C2 crystal phase is clearly visible, and the intercrystalline distance is

[0149] [Example 8]

[0150] The method of Example 1 was followed except that step (4) was carbonized by heating the mixture of 20 vol% C2H4 and CO (30 vol% C2H4, 70 vol% CO) / 80 vol% N2 gas at 15°C / min to 450°C at a pressure of 0.5 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 450℃ for 14 hours.

[0151] Finally, the catalyst was obtained, and the TEM image of the catalyst was Figure 1 and Figure 2 Similarly, the χ-Fe5C2 crystal phase is clearly visible, and the intercrystalline distance is

[0152] [Example 9]

[0153] The method of Example 1 was followed except that step (3) was carried out by reducing the catalyst using 20% ​​by volume H2 / 80% by volume N2 gas at a temperature of 15°C / min to 450°C; the catalyst was heated to 450°C at a pressure of 0.5 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , maintain 450℃ for 20 hours.

[0154] Finally, the catalyst was obtained, and the TEM image of the catalyst was Figure 1 and Figure 2 Similarly, the χ-Fe5C2 crystal phase is clearly visible, and the intercrystalline distance is

[0155] [Example 10]

[0156] The method of Example 1 is followed, except that in step (2), the pH value of the slurry is adjusted with aqueous ammonia so that the pH value of the mixed slurry is 1.0.

[0157] Finally, the catalyst was obtained, and the TEM image of the catalyst was Figure 1 and Figure 2 Similarly, the χ-Fe5C2 crystal phase is clearly visible, and the intercrystalline distance is

[0158] [Comparative Example 1]

[0159] The method of Example 1 was followed except that step (4) was carbonized by heating the mixture to 350°C at 5°C / min with 100% by volume CO at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h. -1 ·g -1 , 350℃ for 20 hours.

[0160] Finally, the catalyst was obtained, and the TEM photo of the catalyst is as follows Figure 3 and Figure 4 As shown, no clear χ-Fe5C2 crystal phase is observed, only Fe-like x C y Crystalline phase of the mixture.

[0161] [Comparative Example 2]

[0162] The method of Example 1 was followed except that step (4) was carbonized by heating to 350°C at 5°C / min with 100% by volume N2 at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 350℃ for 20 hours.

[0163] Finally, the catalyst was obtained, and the TEM image of the catalyst was Figure 3 and Figure 4 Similar, no clear χ-Fe5C2 crystal phase is observed, only Fe-like x C y Crystalline phase of the mixture.

[0164] [Comparative Example 3]

[0165] The method of Example 1 was followed except that step (4) was carbonized by using 100 vol% C2H4, heating to 350°C at 5°C / min, and heating at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 350℃ for 20 hours.

[0166] Finally, the catalyst was obtained, and the TEM image of the catalyst was Figure 3 and Figure 4 Similar, no clear χ-Fe5C2 crystal phase is observed, only Fe-like x C y Crystalline phase of the mixture.

[0167] [Comparative Example 4]

[0168] The method of Example 1 was followed except that step (4) was carbonized by using 100% by volume C3H6, heating to 350°C at 5°C / min, and heating at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h -1 ·g -1 , 350℃ for 20 hours.

[0169] Finally, the catalyst was obtained, and the TEM image of the catalyst was Figure 3 and Figure 4 Similar, no clear χ-Fe5C2 crystal phase is observed, only Fe-like x C y Crystalline phase of the mixture.

[0170] [Comparative Example 5]

[0171] The method of Example 1 was followed except that step (4) was carbonized by heating the mixture to 350°C at 5°C / min with 50% by volume CO / 50% by volume N2 at a pressure of 1.0 MPa, a catalyst loading of 100 g, and a catalyst load of 4000 mL·h. -1 ·g -1 , 350℃ for 20 hours.

[0172] Finally, the catalyst was obtained, and the TEM image of the catalyst was Figure 3 and Figure 4 Similar, no clear χ-Fe5C2 crystal phase is observed, only Fe-like x C y Crystalline phase of the mixture.

[0173] [Test Example 1]

[0174] The catalysts prepared in Examples 1 to 10 and Comparative Examples 1 to 5 were evaluated respectively. The synthesis gas was used to directly prepare light olefins under the following conditions. The results are shown in Table 1.

[0175] The reactor and process conditions are as follows:

[0176] Fluidized bed reactor

[0177] Reaction temperature 330℃

[0178] Reaction pressure 2.0MPa

[0179] The catalyst loading is equivalent to 100g of catalyst before reduction

[0180] Based on the amount of catalyst before reduction, the catalyst loading was 3000 mL·h -1 ·g -1

[0181] Raw material ratio (molar) H2 / CO=2 / 1.

[0182]

[0183]

[0184] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this field, under the technical enlightenment provided by the present invention, as common knowledge in the field, other equivalent variations and improvements can also be made, which should also be regarded as the protection scope of the present invention.

Claims

1. A catalyst for preparing light olefins from synthesis gas, the catalyst having a χ-Fe5C2 crystal face, the catalyst comprising a carrier and an active component, wherein: In terms of atomic ratio, the chemical formula of the active component is as follows: Faith 100 Mn a The b Cr c D d AND e OH x , D is selected from at least one of alkaline earth metals; E is selected from at least one of the lanthanide rare earth elements; The value range of a is 30.0~120.0; The value range of b is 5.0~50.0; The value range of c is 1.0~30.0; The value range of d is 0.1~10.0; The value range of e is 0.1~10.0; x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst; The preparation method of the catalyst for preparing light olefins from synthesis gas comprises: (1) mixing a solution containing an Fe precursor with a solution containing a Mn precursor, a Cu precursor, and a Cr precursor to obtain a solution I; (2) precipitating the solution I with an alkaline precipitant, and washing the precipitate to obtain a precipitate; (3) mixing the precipitate with a carrier sol and an alkaline earth metal precursor solution in sequence, adjusting the pH value of the slurry, mixing with a lanthanide rare earth element precursor solution, drying, forming and calcining to obtain an iron-based catalyst intermediate; (4) The iron-based catalyst intermediate is subjected to reduction and carbonization treatment; Wherein, the atmosphere of the carbonization treatment is a mixed gas containing olefins, CO and N2.

2. The catalyst according to claim 1, characterized in that The crystal spacing of the catalyst is 4.8~5.4Å.

3. The catalyst according to claim 1, characterized in that The alkaline earth metal is selected from at least one of Be, Mg, Ca, Sr and Ba; and / or the lanthanide rare earth element is selected from at least one of La, Ce, Pr and Nd.

4. The catalyst according to claim 1, characterized in that The value range of a is 40.0~110.0; The value range of b is 10.0~40.0; The value range of c is 5.0~25.0; The value range of d is 0.5~8.0; The value range of e is 0.5~8.

0.

5. The catalyst according to any one of claims 1 to 4, characterized in that The carrier is selected from at least one of silicon dioxide, aluminum oxide and titanium oxide, and / or, based on the weight of the catalyst, the content of the carrier is 5-60% by weight.

6. The catalyst according to any one of claims 1 to 4, characterized in that The reduction treatment conditions include: a pressure of 0-2 MPa; and / or a catalyst load of 3000-6000 mL·h -1 ·g -1 ; and / or, the temperature is 200-550°C; and / or, the time is 12-48 hours; and / or, the heating rate is 1-15°C / minute; and / or, The atmosphere for the reduction treatment is a mixed gas containing H2 and N2.

7. The catalyst according to claim 6, characterized in that Based on the total volume of the mixed gas, the volume concentration of H2 is 1% to 20%, and the volume concentration of N2 is 80% to 99%.

8. The catalyst according to any one of claims 1 to 4, characterized in that The carbonization treatment conditions include: a pressure of 0-2 MPa; and / or a catalyst load of 3000-6000 mL·h -1 ·g -1 ; and / or, the temperature is 200-550°C; and / or, the time is 12-48 hours; and / or, the heating rate is 3-20°C / minute; and / or, The olefin is C2H4 and / or C3H6.

9. The catalyst according to claim 8, characterized in that Based on the total volume of the mixed gas, the total volume concentration of olefins and CO is 10% to 60%; the volume concentration of N2 is 40% to 90%.

10. The catalyst according to claim 9, characterized in that Based on the total volume concentration of olefins and CO, the volume concentration of olefins is 10%~50%; the volume concentration of CO is 50%~90%.

11. The catalyst according to any one of claims 1 to 4, characterized in that Adjust pH to 1-6.

12. The method for preparing the catalyst for preparing light olefins from synthesis gas according to any one of claims 1 to 11, characterized in that: include: (1) mixing a solution containing an Fe precursor with a solution containing a Mn precursor, a Cu precursor, and a Cr precursor to obtain a solution I; (2) precipitating the solution I with an alkaline precipitant, and washing the precipitate to obtain a precipitate; (3) mixing the precipitate with a carrier sol and an alkaline earth metal precursor solution in sequence, adjusting the pH value of the slurry, mixing with a lanthanide rare earth element precursor solution, drying, forming and calcining to obtain an iron-based catalyst intermediate; (4) The iron-based catalyst intermediate is subjected to reduction and carbonization treatment; Wherein, the atmosphere of the carbonization treatment is a mixed gas containing olefins, CO and N2.

13. A method for directly preparing light olefins from synthesis gas, comprising: In the presence of the catalyst for preparing light olefins from synthesis gas as claimed in any one of claims 1 to 11 or in the presence of the catalyst for preparing light olefins from synthesis gas obtained by the preparation method according to claim 12, H2 is contacted with CO for reaction.

14. The method according to claim 13, characterized in that The reaction temperature is 200-600°C; And / or, the reaction pressure is 0.5~10MPa; and / or, based on the amount of catalyst before reduction, the volumetric space velocity of the synthesis gas is 100-8000 mL·h -1 ·g -1 ; and / or, the H2 / CO molar ratio in the synthesis gas is 0.1 to 5; And / or, the low-carbon olefin is a C2~C4 olefin.

Citation Information

Patent Citations

  • Sintered iron catalyst for Fischer-Tropsch Synthesis and preparation method and application thereof

    CN1704161A

  • A catalyst and a method for preparing ethene by directly converting synthetic gas

    CN108568311A

  • Method for preparing low-carbon olefin from synthesis gas

    CN112625726A